THE ROLE OF ENGLISH FOR SPECIFIC PURPOSES (ESP) IN ENGINEERING EDUCATION (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This paper explores the significance of English for Specific Purposes (ESP) in engineering education. As the global demand for English-speaking professionals in technical fields grows, ESP emerges as a vital component of academic programs in engineering institutions. The study highlights how ESP bridges the gap between general language skills and technical communication needs, focusing on field-specific vocabulary, professional writing, and effective oral communication.